From preferences to concerted policy on mandated share for renewable energy in transport. (August 2021) - Kulisic, Biljana; Dimitriou, Ioannis; Mola-Yudego, Blas
Abstract: Environmental, energy, transport and agriculture policies are intersecting when deciding on renewable energy in transport (RES-T) implementation strategies. The uncertainty related to the advanced biofuels, limitations and underperformance of readily available technologies for decarbonization of transport sector challenges RES-T policy making. This paper employs partitioning as a choice architecture tool to create a concerted RES-T policy. The approach collects the preferred attributes of an alternative fuel rather than the preferred fuel by guiding stakeholders through RES-T policy, ensuring that all aspects of concerted policy are covered. Fuzzy analytical hierarchical process (fAHP) has been superimposed on the partitioning related to the biofuels to mathematically weight the alternatives. fAHP ranks the weighted preferences on biofuels to build a consensus among stakeholder groups, later translated to the actual RES-T mix, quantities and investments needed to meet the mandated share. Applied on Croatia, the preferences of three stakeholder groups were weighted and ranked; whereas some discrepancies were identified, the consensus outlined the national transport decarbonization policy with related investments. When the consensual RES-T mix contrasted with the least-cost alternative, the investment needed was reduced to a quarter. The collaborative management process proved to be a time-effective participatory approach for a silo-based policy structure. Highlights: Partitioning as a choice architecture with fuzzy AHP for concerted transport policy. Targeted stakeholders at Ministries, Energy institutes & Energy Strategy Committee. Results of consensus preferences cost ×4 times the least-cost alternatives. Participatory approaches recognizing complexities key for able RES-T policies.